Analysis of Mental Symptoms in the World of Education - Badrul Islam; Muhammad Hasan Maulana (al-Afkar, Journal For Islamic Studies, 2026)
Humans as social beings have highly diverse psychological aspects, and understanding these psychological symptoms is crucial for comprehending mental processes experienced by all individuals. This research aims to identify psychological symptoms in students. The approach used in this study is qualitative with library research methodology. The research results show that psychological symptoms in students are divided into three categories: emotions (emotions, theories of emotion and motivation), cognitive symptoms including (memory, perception, intelligence, thinking and language), and conative symptoms including (motives of inference, explanation and prediction, motive circle, frustration and conflict). However, this research focuses only on discussing psychological symptoms in emotional and cognitive aspects. Therefore, further research is needed that comprehensively discusses conative symptoms along with case studies.